Chronic exposure of low dose organic arsenic induced microscopic changes in rat’s kidney - Wan Salleh, Wan Muhamad Salahudin; A.Talib, Norlelawati; Abdullah, Nor Zamzila; Aung, Sanda; Buyong, Zunariah (2019)
Introduction: Monosodium methylarsonate (MSMA) is an organic arsenic widely used in agriculture. Humans are exposed to arsenic through drinking water and anthropogenic activities. Chronic exposure to inorganic arsenic has been linked with multiple health problems. However, studies focusing on organic arsenic effects on kidneys were limited. Objective: To determine the effects of organic arsenic exposure on rat’s kidney. Materials and Method: Twelve male Sprague-Dawley rats were divided into control (n=6) and treated (n=6) groups. Control group was given daily oral gavage of distilled water and treated group was given daily oral gavage of MSMA at 63.0 mg/kg body weight, which was equivalent of 1/30 LD50 of MSMA. After four months, rats urines were collected using metabolic cage and both groups were sacrificed. The urines were analyzed using enzyme-linked immunosorbent assay (ELISA) for neutrophil gelatinase-associated lipocalin (NGAL) biomarkers for kidney injury. The kidneys were harvested for light microscopy study. Results: Urine NGAL significantly higher (p-value <0.05) in treated groups. Light microscopy showed focal glomerular and tubular changes in treated groups. Conclusion: Chronic low dose organic arsenic exposure induced kidney injury.